S SINTESIS DAN UJI AKTIVITAS ANTIBAKTERI SENYAWA 3ꞌ-BROMO-4-METOKSI KALKON TERHADAP BAKTERI Staphylococcus aureus DAN Escherichia coli - Rahma Dona; Haiyul Fadhli; Adel Zamri; Winda Tria Safitri; Abdi Wira Septama (Jurnal Penelitian Farmasi Indonesia, 2022)
Chalcone is a flavonoid derivative that has a variety of interesting biological activities. One of the compounds suspected of being an antibacterial agent is chalcone. The properties of chalcone compounds depend on the substituents that depend on the two aromatic rings, such as Cl, Br, OH groups and so on. The purpose of this study was to synthesize chalcone analogue compounds and determine the potential of these analog compounds as antibiotics. In this research, a chalcone analogue compound has been successfully synthesized, namely 3ꞌ-Bromo-4-methoxy-chalcone through the stirring method using KOH catalyst, ethanol solvent. The results of the synthesis carried out by recrystallization and the yield obtained were 64 %. Identification of compounds that have been carried out by TLC test, melting point, and HPLC analysis. The structure of the compound was characterized by UV-Vis spectroscopy, FTIR and 1H NMR, indicating that the analogue chalcone compound has a structure as expected. Testing the activity of chalcone analogue compounds was carried out on Staphylococcus aureus and Escherichia coli at a concentration of 1%, 5%, 10% and 20% test solutions. The test results showed that the antibacterial activity of the compound 3ꞌ-Bromo-4-methoxy-chalcone was categorized as weak.